Anticoagulants, Antiplatelets, and Thrombolytics - Mousa, Shaker ; Ed (Methods in Molecular Medicine, 93, 2004)
Featuring a collection of review articles that highlights the development of antithrombotics, this work provides experimental methods for the further development of new and improved anticoagulants. Among the cutting-edge developments reviewed are the novel usage of low molecular weight heparins, such antithrombin agents as the hirudin.